A comparison of results from geomorphological diversity evaluation methods in the Polish Lowland (Toruń Basin and Chełmno Lakeland). Issue 1 (2nd January 2018) - Kot, Rafał
Abstract: Geomorphological diversity is part of geodiversity. Study and evaluation of geodiversity, including geomorphological diversity, is often conducted in uplands and mountains, despite the fact that lowland areas are of equal importance. This paper evaluates geomorphological diversity in a small area of the Polish Lowland, using a variety of methods that have been applied in recent times for evaluating geodiversity, and presents the results on maps. By comparing these maps and analyzing the correlation coefficients of the results obtained, it was possible to identify the two methods that were best suited to indicating areas with the greatest geomorphological diversity in the lowlands. These two methods are least affected by the choice of elementary fields and data classification methods applied. The study identified the two areas with the greatest relief diversity and showed that they distinctly differ from one another. They demonstrate the major influence of processes, not only on the topographic parameters and landform types, but above all on identifying and defining total geomorphological diversity. These methods, which can be used to identify the areas with the greatest total geomorphological diversity, could readily be used in applied studies relating to abiotic ecosystem services and landscape management.